A sampling study of branching characteristics towards obtaining more efficiency for tree selection in breeding trials - Gwebu, Simosabo Bhekinkhosi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.